Kemampuan Teknis Sumber Daya Manusia dalam Pengelolaan Arsip di Dinas Perpustakaan dan Kearsipan Kabupaten Gorontalo - Humolungo, Sriyulianti; Djafar, Franky; Luwao, Salma Rivani (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2025)
This study aims to analyze the technical capacity of human resources in archival management at the Library and Archives Office of Gorontalo Regency, as well as to identify inhibiting factors and formulate strategies to enhance the effectiveness of archival governance. Employing a descriptive qualitative approach, data were collected through in-depth interviews, direct observation, and documentation. Eight informants were purposively selected based on their direct involvement in archival operations. The findings reveal that technical competencies remain low, as reflected in the limited understanding of archival classification, the use of e-Archives applications, and archival disposal procedures. Key contributing factors include the lack of ICT-based training, absence of professional mentoring, and inadequate digital infrastructure. These issues are further exacerbated by weak administrative systems, ineffective internal and external communication, and the gap between theoretical knowledge and practical implementation. Practically, this study recommends strengthening technical capacity through intensive training programs and the development of a structured and inclusive competency roadmap. Theoretically, the study contributes to the body of knowledge on local archival governance in the context of digital transformation and bureaucratic reform. Future research may explore the effectiveness of digital-based archival training interventions or conduct comparative studies across regions to identify best practices in local government archival management.